Technological Advancements and Economics in Plant Production Systems: How to Retrofit? - Uyeh, Daniel Dooyum; Mallipeddi, Rammohan; Park, Tusan; Woo, Seungmin; Ha, Yushin (Frontiers in Plant Science, 2022)
Plant production systems such as plant factories and greenhouses can help promote resiliency in food production. These systems could be used for plant protection and aid in controlling the micro- and macro- environments needed for optimal plant growth irrespective of natural disasters and changing climate conditions. However, to ensure optimal environmental controls and efficient production, several systems such as sensor systems and robots have been developed and are at different stages of implementation. New and improved systems are continuously being investigated and developed with advances in technologies such as robotics, sensing, and artificial intelligence to mitigate hazards to humans working in these systems from poor ventilation and harsh weather while improving productivity. These technological advances necessitate frequent retrofits considering local contexts such as present and projected labor costs. The type of agricultural products also affects measures to be implemented to maximize returns on investment. Consequently, we formulated the retrofitting problem for plant production systems considering two objectives; minimizing the total cost for retrofitting and maximizing the yearly net profit. Additionally, we considered the following: a) cost of new technologies; b) present and projected cost for human labor and robotics; c) size and service life of the plant production system; d) productivity before and after retrofit, e) interest on loans for retrofitting, f) energy consumption before and after retrofit and, g) replacement and maintenance cost of systems. We solved this problem using a multi-objective evolutionary algorithm that results in a set of compromised solutions and performed several simulations to demonstrate the robustness of the method. Results showed up to a 250% increase in annual net profits in an investigated case, indicating that the availability of all the possible retrofitting combinations would improve decision making. A user-friendly system was developed to provide all the possible feasible retrofitting combinations and total costs with the yearly return on investment in a single run.